COMPREHENSIVE FRAMEWORK FOR SOCIAL MEDIA MARKETING (SMM) STRATEGY FOR EFFECTIVE BUSINESS ACTIVITY - Chyrak, Iryna; Koziuk, Viktor; Siskos, Evangelos; Darvidou, Konstantia (Socio-economic relations in the digital society, 2024)
This study develops a comprehensive framework for social media marketing (SMM) strategies aimed at enhancing business effectiveness. It begins by examining the transformative role of digital technologies in reshaping business practices, particularly through SMM. A detailed review of the literature explores the impact of SMM on business growth, brand awareness, and customer engagement while identifying key challenges such as resource limitations and measuring ROI.The research synthesizes theoretical foundations, including relationship marketing and user engagement models, to highlight essential components of an effective SMM strategy. These components include goal definition, audience analysis, competitive benchmarking, platform selection, content strategy development, implementation and scheduling, community engagement, analytics and optimization evaluation and reporting. The study also emphasizes the role of modern technologies, such as artificial intelligence, big data analytics, and automation tools, in streamlining SMM operations.A proposed framework integrates strategic planning, audience engagement, content creation, and performance monitoring, at the same time adapting to changeable market dynamics and consumer preferences. Case studies illustrate successful applications across industries, providing practical insights into overcoming common barriers to SMM implementation. This research contributes actionable strategies for businesses seeking to leverage SMM as a key driver of operational success and competitive advantage.
Keywords: social media; social media marketing; SMM strategy; SMART; target audience; competitive benchmarking; social media platform; content strategy; users engagement